Male reproduction and environmental and occupational exposures: a review of epidemiologic methods Reproducción masculina y exposiciones ambientales u ocupacionales: una revisión de métodos epidemiológicos - Anne L. Golden; Jacqueline M. Moline; Natan Bar-Chama (Instituto Nacional de Salud Pública, 1999)
Concerns that chemical exposures in the environment have been detrimental to male sexual development and fertility have been heightened by reports of declining sperm counts over the past 50 years. Marked geographic variation has been found in semen quality and in the incidence of testicular cancer and certain urogenital defects. Debate continues over the existence, magnitude and significance of these trends, and how best to evaluate the hypothesis that in utero and childhood exposures to estrogenic compounds may be to blame. Epidemiologic methods for assessing the impact of hazardous substances on male reproductive health have been developed mainly in the area of occupational medicine, and this paper will review the currently recommended methods. These include questionnaires to determine reproductive history and sexual function; reproductive hormone profiles; and semen analyses such as sperm concentration, motility, and morphology. New research tools that show significant promise from the fields of clinical reproductive medicine and reproductive toxicology are discussed as possible additions to epidemiologic studies, including assays of sperm function and genetic integrity, and biomarkers of DNA damage. For population-based studies involving occupational groups or communities with environmental exposures, issues related to the cost, validity, precision and utility of these methods must be carefully considered. Varios artículos publicados informan acerca de una declinación en la concentración de espermatozoides durante los últimos 50 años; lo anterior ha motivado una preocupación creciente en el sentido de que las exposiciones ambientales a diversos químicos actúen en detrimento del desarrollo sexual y de la fertilidad masculina. Se ha observado una marcada variación geográfica en la calidad del semen y en la incidencia del cáncer testicular y diversas malformaciones urogenitales. Persiste un debate acerca de la existencia, magnitud y significado de estos fenómenos y también acerca de la mejor forma para evaluar la hipótesis de que sus causas son las exposiciones in utero a compuestos estrogénicos. En este trabajo se revisan los métodos epidemiológicos recomendables para evaluar el impacto de sustancias peligrosas sobre la salud reproductiva masculina, varios de los cuales provienen del área de la medicina ocupacional. Se incluyen los cuestionarios para determinar la historia reproductiva y la función sexual; los perfiles de hormonas reproductivas, y los análisis de semen para medir concentración, morfología y motilidad. También se discute la posibilidad de utilizar para la investigación una serie de nuevas herramientas que provienen de la medicina y de la toxicología reproductivas, entre ellas los ensayos de la función espermática y la integridad genética y los biomarcadores de daño al DNA. Se deben tomar cuidadosamente en consideración los aspectos relativos a la utilidad, validez, precisión y costos de estos métodos para la realización de estudios poblacionales, ya sea que involucren grupos ocupacionalmente expuestos y/o comunidades con exposiciones ambientales.